al-Marrār b. Munqidh’s Life and Poetry - Esat Ayyıldız (Rize İlahiyat Dergisi, 2024)
In the scholarly examination titled “al-Marrār b. Munqidh’s Life and Poetry”, a focused lens is turned towards the somewhat elusive figure of al-Marrār b. Munqidh, shedding light on his life and, more notably, his poetic contributions during the Umayyad era. The article’s methodological approach centers on a twofold analysis, first drawing from the limited biographical data available about al-Marrār to paint a picture of the poet and his socio-cultural environment, and then engaging in a meticulous exploration of his poetic oeuvre to discern the thematic and stylistic choices that characterized his work. Subject-wise, the research emphasizes the importance of studying lesser-acknowledged poets like al-Marrār b. Munqidh to fill gaps in the collective understanding of the Umayyad poetic landscape. His verses, although not dominantly featured in current literary circles, are intricate tapestries weaving the sentiments, intellect, and cultural motifs of his age. Thus, through his poetry, readers and scholars can glean nuanced insights into the multifaceted world of the Umayyad era, making his works indispensable for anyone seeking a comprehensive grasp of the period’s literary milieu. Regarding scope, while the article does delve into al-Marrār b. Munqidh’s biography, it primarily emphasizes the exploration of his poetry. Given the paucity of detailed records about his life, the emphasis on his poetic works is not just a choice but a necessity. This, in turn, allows the article to cast a wide net over the expanse of Umayyad poetry, positioning al-Marrār's contributions within this broader framework. By juxtaposing his poetic techniques and themes with those of his contemporaries, the research offers a holistic perspective on the dynamics and divergences that marked the Umayyad poetic tradition. The article underscores the importance of al-Marrār b. Munqidh not just as a poet, but as a key to unlocking the subtleties of his age. His poetry, with its distinctive thematic concerns and stylistic elements, becomes a mirror reflecting the broader societal, cultural, and intellectual shifts of his time. By studying his works, the research asserts that one can gain a deeper understanding of the underlying currents that shaped the artistic expressions of the Umayyad poets. As for the research’s purpose, it is manifold. Firstly, it aims to bring to the fore the life and works of a poet who might otherwise remain on the periphery of Arabic literary studies. In doing so, it not only champions the cause of al-Marrār b. Munqidh but also underscores the need to continually revisit and reassess historical literary figures, thereby preventing them from fading into obscurity. Furthermore, by anchoring its analysis in the broader context of Umayyad poetry, the research endeavors to enrich our understanding of the epoch, drawing attention to the intricacies and innovations that defined it. Methodologically, the research adopts a blended approach. It employs historical analysis to piece together the scant details of al-Marrār b. Munqidh’s life, cross-referencing various sources to ensure accuracy and reliability. Simultaneously, for the exploration of his poetry, a close textual analysis is employed.